Gender Equality among Employees of a State University System - Dimas, Ruby B. (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to assess gender equality among employees focusing on: rights, duties, benefits/privileges and opportunities. The descriptive method was employed using validated questionnaire and conducting interview to a sample of 432 employees of Isabela State University System. Data gathered were analyzed through the SPSS, frequency counts, percentage, weighted mean and f-test. Gender equality as to rights reveal that the respondents strongly agree that husbands and wives deserve equal respect by the family members; parents should give their sons and daughters equal access to education; and agree that husbands and wives should have equal roles in decisions on investments and spending money. As to duties, they agree that loyalty of both spouses should be observed; and must have equal responsibility in providing the needs of the family. In terms of benefits and privileges, they strongly agree that husbands and wives should be provided with equal medical care including their sons and daughters; they agree that men and women should have equal chance for promotion at work; accomplishment of both spouses must be given due recognition; parents should provide daughters with as much inheritance as sons, and as much authority over the use of the inherited funds. As to opportunities, they agree that both sexes should have equal opportunities to become leaders and heads of offices and organizations; employment opportunities are open for both; and to be engaged in income generating activities; social and recreational activities. Their view on gender equality is not associated with their profile. This result will lead to development of both sexes; and economic stability of the society will be attained. Thus, advocacy for gender equality should be sustained and strengthened.